Quality of life,Eczema area, Disease severity and some selected factors related to Atopic Dermatitis among children attending the Dermatology Clinic at Lady Ridgeway Hospital. - Herath, H.M.L (My University, 2006)
To determine the sensitivity of U.K working party diagnostic criteria and the quality of life, eczema area, disease severity and describe selected factors related to atopic dermatitis among children attending the dermatology clinic at the Lady Ridgeway hospital. The study was a descriptive cross-sectional study. The study population composed of 425 doctor diagnosed children with AD. The sensitivity of U.K. working party criteria is more or less equal to the previous studies and reliable to use in epidemiological studies QOL questionnaire and DFI questionnaire are good tools to assess QOL OF our children and families with AD.EASI is a useful index to assess eczema area and disease severity in Clinic settings in Sri Lanka but may need modifications